Martin Lipscomb: "Questioning the Use Value of Qualitative Research Findings" (2012) - Paley, John (Nursing philosophy, 2025)
This article discusses a paper by Martin Lipscomb, published in 2012. Martin's paper asks whether the findings in qualitative nursing research can provide evidence robust enough to inform nursing practice. Martin appraises various arguments designed to establish that qualitative studies do provide a basis for action, and concludes that they fail. I provide a commentary on the paper, and then look at more recent attempts to vindicate the use value of qualitative research. I argue that the question "What requirements must qualitative studies meet if they are to serve as a basis for future action?" has only one persuasive answer. Unfortunately, the relevant requirements are not met by the majority of qualitative studies in nursing.